Smart Home Simulation / Ahmad Jazzri Jamaludin - Ahmad Jazzri , Jamaludin (2003)
The project entitled "Smart Home Simulation" is a project that shows simulating of Smart Home in a real wrld application. This simulation system is a simulation just like other simulation system such as circuit simulator which show exactly like a real application of how does it work.This project emphasize in how to control the system via Internet. In order to simulate how the system will operate, this project consist a usa interface, a virtual home module and simulation control. The user interface and simulation control will be installed in one computer and a virtual home module in another. These computers will be connected to the Internet or LAN in order to act like controlling home from anywhere order the net. controller or hi-tech or gadjet or even a simple circut. This project is totally a simulation system to guide people to understand how does it work in general and help them how to manage the house with this brand new technology system This project involving developing a user interface, virtual home module and simulation control module to make these computers that contain these two modules communicate with each other. At the end of this project, The Smart Home Simulation is expected to be such as other simulator that existence to provide an overview to understanding about real world Smart Home especially to customer that interested to own this technology in their home.